Association Between Race and Ethnicity and Hip Fracture Outcomes in a Universally Insured Population. (5th July 2018) - Okike, Kanu; Chan, Priscilla H.; Prentice, Heather A.; Paxton, Elizabeth W.; Navarro, Ronald A.
Abstract : Background: Prior studies have documented racial and ethnic disparities in hip fracture treatment and outcome, and unequal access is commonly cited as a potential mediator. We sought to assess whether disparities in hip fracture outcome persist within a universally insured population of patients enrolled in a managed health-care system. Methods: A U.S. integrated health systems registry was used to identify patients who underwent treatment for a hip fracture when they were ≥60 years of age from 2009 to 2014. Patient demographics, procedure details, and outcomes were obtained from the registry. Differences in outcome according to race/ethnicity were analyzed using multivariable regression analysis with adjustment for socioeconomic status and other potential confounders. Results: Of 17, 790 patients, 79.4% were white, 3.9% were black, 9.4% were Hispanic, and 7.4% were Asian. Compared with white patients, black patients had a similar 1-year mortality rate (odds ratio [OR] = 0.93, 95% confidence interval [CI] = 0.79 to 1.09, p = 0.37), Hispanic patients had a lower rate (OR = 0.85, 95% = CI = 0.75 to 0.96, p = 0.01), and Asian patients also had a lower rate (OR = 0.65, 95% CI = 0.56 to 0.76, p < 0.001). There were no differences in terms of surgical delay, 90-day emergency department visits, or reoperations during the patient's lifetime (p > 0.05) between the groups. Compared with white patients, black and Hispanic patients had fewer 90-day postoperative complications (p = 0.04 and p = 0.01, respectively); 90-day unplanned readmissions were less common among Asian patients (p = 0.03) but more common among black patients (p = 0.01). Conclusions: In this study of hip fractures treated in an integrated managed care system, minority patients were found to have postoperative mortality rates that were similar to, or lower than, those of white patients. These findings may be related to the equal access and/or standardized protocols associated with treatment in this managed care system. Level of Evidence: PrognosticLevel III . See Instructions for Authors for a complete description of levels of evidence.